Antwerpen : de haven - Van Cauwenbergh, George; Van Cauwenbergh, Dis; Craeybeckx, Lode (Antwerpen: Ontwikkeling, 1961)
"George en Dis Van Cauwenbergh ; ten geleide Lode Craeybeckx Bibliotheek Camille Huysmans"